2013
DOI: 10.1021/jf400888c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Series of Monosaccharide–Fipronil Conjugates and Their Phloem Mobility

Abstract: To test the effect of adding different monosaccharide groups to a non-phloem-mobile insecticide on the phloem mobility of the insecticide, a series of conjugates of different monosaccharides and fipronil were synthesized using the trichloroacetimidate method. Phloem mobility tests in castor bean ( Ricinus communis L.) seedlings indicated that the phloem mobility of these conjugates varied markedly. L-Rhamnose-fipronil and D-fucose-fipronil displayed the highest phloem mobility among all of the tested conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Glucose and amino acid promoieties were introduced into insecticides to develop phloem‐targeted proinsecticides (Table ). The resulting derivatives included glycinyl fipronil conjugate, sugar‐fipronil conjugates, D‐glucose‐rotenone conjugates, glycinergic‐fipronil conjugate, and amino acid‐chlorantraniliprole conjugates . Despite their parent compounds lack of mobility in the phloem, several of the above mentioned insecticide conjugates had good phloem systemicity .…”
Section: Carrier‐mediated Propesticide Strategies For Improving Agrocmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose and amino acid promoieties were introduced into insecticides to develop phloem‐targeted proinsecticides (Table ). The resulting derivatives included glycinyl fipronil conjugate, sugar‐fipronil conjugates, D‐glucose‐rotenone conjugates, glycinergic‐fipronil conjugate, and amino acid‐chlorantraniliprole conjugates . Despite their parent compounds lack of mobility in the phloem, several of the above mentioned insecticide conjugates had good phloem systemicity .…”
Section: Carrier‐mediated Propesticide Strategies For Improving Agrocmentioning
confidence: 99%
“…The resulting derivatives included glycinyl fipronil conjugate, sugar‐fipronil conjugates, D‐glucose‐rotenone conjugates, glycinergic‐fipronil conjugate, and amino acid‐chlorantraniliprole conjugates . Despite their parent compounds lack of mobility in the phloem, several of the above mentioned insecticide conjugates had good phloem systemicity . The vacuolar sequestration of sugar and glutathione conjugates via ABC transporters which occurs in planta during the final detoxification process of agrochemicals may reduce the phloem loading of these synthetic conjugates.…”
Section: Carrier‐mediated Propesticide Strategies For Improving Agrocmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the Bonnemain group has reported several derivatives of existing herbicides modified with an α ‐amino acid fragment that exhibit good phloem mobility . In our previous work, a series of glucose–fipronil conjugates (GTF and GOF) and a glycinergic–fipronil conjugate (GlyF) that show distinctive distributions in Ricinus communis have been designed . The uptake of these conjugates was proven to be mediated by an endogenous carrier system .…”
Section: Introductionmentioning
confidence: 99%
“…2,10 In addition, 10 kinds of fipronil-monosaccharide derivatives were synthesized in our previous work ( Figure 1). 11 Most of these derivatives have been verified as having phloem systemicity. These studies revealed that conjugating glucose or another monosaccharide can confer phloem mobility on a nonphloem-mobile insecticide.…”
Section: ■ Introductionmentioning
confidence: 99%